Estimation Level of Leptin and Resistin in Sera Patients with Type Two Diabetes among Iraqi Peoples (Medico Legal Update, 2020)
Leptin it is a protein hormone containing 167 amino acids, firstly discovered in 1994 by Jeffrey M. Friedman,It is secreted by adipocytes and has been found to regulate food intakes through central neuroendocrinemechanisms. Resistin has been found to be generated and released via adipose tissue to serve endocrinefunctions which are likely to be associated with insulin resistance.Aim: The aim of this study determination of leptin and resistin hormone level in serum of male and femalewith type 2 diabetic patients and healthy control in Iraq.Subject and Method: This respective study carried out at three main medical facilities in Baghdad; NationalCenter For Teaching Laboratories, Poisoning Consultation Center/Specialized Surgeries Hospital and theNational Blood Transfusion center in Medical City,Iraq during the period from November 2019 to February2020. It was included 100 participants; divided into 2 groups(50 patient with type 2 diabetes and 50 healthycontrol).Results: The result of serum leptin showed that there was highly significant difference when comparing themean of total serum leptin of patient group with that of the control group. While the mean of total circulatingresistin in T2DM patient and healthy with no significant difference between the two groups.Conclusion: Increased serum leptin level in type 2 diabetes patient than healthy control and no significantdifference in serum resistin level when compared between diabetics and control